In vivo study of the radioadaptive response and low-dose hyper-radiosensitivity for chromosome breaks induced by gamma rays in wild-type Drosophila melanogaster larval neuroblasts: Dose and dose rate dependence - Claudia Di Dio; Antonella Porrazzo; Alex De Gregorio; Patrizia Morciano; Maria Antonella Tabocchini; Giovanni Cenci; Francesca Cipressa; Giuseppe Esposito (PLoS ONE, 2025)
Although the biological effects of low doses/dose rates of ionising radiation have been extensively studied both i n vitro and in vivo , there are still knowledge gaps to be filled. For example, the mechanisms underlying the phenomena of radioadaptive responses and hypersensitivity to low doses of radiation are still not fully understood. This study aims to investigate the phenomenon of radioadaptive response in Drosophila melanogaster larval neuroblasts, focusing on the influence of different gamma priming doses and priming dose rates. We examined the modulation of cytogenetic damage, specifically the frequency of chromosome breaks, induced by a challenging dose of 10 Gy following different priming doses (0–2.7 Gy) delivered at dose rates ranging from 1.4 to 17 mGy/h. Our findings reveal the presence of a distinct window in which radioadaptive responses occurs, notably above a certain threshold dose when delivered at a rate of 1.4 mGy/h. Consistently with our previous results, we confirmed that the maximal protection was observed at a priming dose of 0.4 Gy delivered at 2.5 mGy/h. Additionally, we studied the occurrence of chromosome breaks after irradiating larval neuroblasts at doses ranging from 0.7 to 10 Gy. Notably, in this case we observed a low-dose hyper-radiosensitivity phenomenon up to 2.7 Gy, followed by increased resistance above 2.7 Gy. Our results provide insight into the complex cellular responses to low-dose/dose rate radiation and have implications in various fields, including radiation protection, diagnostics, theragnostics and biodosimetry.